2017
DOI: 10.4236/ce.2017.88089
|View full text |Cite
|
Sign up to set email alerts
|

Does Learner-Centred Approach Improve High School Learners’ Understanding of Acids and Bases Topic? A Case of Two Selected Secondary Schools in Ohangwena Region, Namibia

Abstract: This paper presents findings on a study that was conducted at two selected secondary schools in Ohangwena educational region in Namibia. The study used a quantitative approach to investigate if using learner-centred approach improves learners' understanding of acids and bases. With a sample of 80 grade 11 learners taking Physical Science Ordinary level, a quasi-experimental design was used to collect data from two schools for two weeks (one week at each school). The Pre-test, post-test scores from the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, the findings are supported with the quantitative information in Table 3 where 83.8 percent of the respondents agreed to the statement that learner centred pedagogy approach promotes learners' motivations in learning. The findings are also in line with those of Mutilifa and Kapenda (2017) who in his study found that learner centred approach attracts the learners' interest in the process of teaching and learning process. Therefore, this study determined that learner centred pedagogy plays an important role in making learners more attracted to the lesson in the process of teaching and learning.…”
Section: Learner Centred Approach Attract Learner Interestsupporting
confidence: 90%
“…Furthermore, the findings are supported with the quantitative information in Table 3 where 83.8 percent of the respondents agreed to the statement that learner centred pedagogy approach promotes learners' motivations in learning. The findings are also in line with those of Mutilifa and Kapenda (2017) who in his study found that learner centred approach attracts the learners' interest in the process of teaching and learning process. Therefore, this study determined that learner centred pedagogy plays an important role in making learners more attracted to the lesson in the process of teaching and learning.…”
Section: Learner Centred Approach Attract Learner Interestsupporting
confidence: 90%
“…Researchers such as (Qhobela & Moru, 2011;Boyle & While, 2004) found that approaches such as study groups, whereby students collaborate and interact in small groups around a topic assigned to them are more likely to make a positive impact on their practice than traditional approaches such as question and answer used in teacher-centered approach. Equally, the findings of (Mutilifa & Kapenda, 2017) showed that usage of various learner-centered approaches improves high school learners' conceptual understanding in physical science (p.1260).…”
Section: Literature Reviewmentioning
confidence: 99%